The Perbandingan Performansi Trainer Unit Instalasi Sistem Refrigerasi dengan Menggunakan Katup Ekspansi Tipe TXV dan Pipa Kapiler - Muliawan, Rizki; Hidayat, Asep; Prasetyo, Bowo Yuli; Akmal, Muhammad (Politeknik Negeri Jakarta, 2023)
Nowadays, food and beverage preservation is very important in maintaining quality. One of them is the cooling method using a refrigeration system. The performance of the Refrigeration System in the trainer unit being compared is the Thermostatic Expansion Valve (TXV) and the Capillary tube with 2 kg of cucumber product. The refrigerant used is R-134a and 2 different types of expansion, namely the capillary tube and Txv. The research aims to determine the performance of the refrigeration system unit trainers from both types of expansion. The research method used is to conduct experiments on the system. Based on the test results, the system using the TXV type has an actual COP value of 3.65 and a Carnot COP of 7.14 for a system efficiency of 51.1%. In contrast to the expansion type Capillary pipe has a value of 4.1 for COPactual and COPcarnot 7.2 and 56.9% for system efficiency. The comparison of electrical energy between using a TXV and a capillary is 0.0950 kWh compared to 0.082 kWh. The results of the comparison above, shows that the system using capillary pipes is better by saving 5.8% compared to the system using TXV-type expansion.